Taiwan’s Mythological Theme Parks: Mnemonic Guardians and Uncanny Imaginaries - Brereton, Brian G. G. (Acta Orientalia Vilnensia, 2006)
Cornell University This paper analyzes the mnemonic roles of mythological theme parks in contemporary Taiwan. I investigate two popular theme parks, Madou’s “Prefecture that Represents Heaven” (代天府) and its single Taiwanese precedent, the “Palace of Southern Heaven” (南天宮) in Zhanghua. I term these sites “mythological theme parks” because they differ significantly in form and function from other popular religious temples throughout Taiwan and China. Though both theme park and temple are loci of social production and reproduction, the nature of interaction at mythological theme parks resembles in many ways that which occurs at the imaginary realms manufactured by secular theme parks. These mythological theme parks feature moral imaginaries displayed in sculptural and animatronic depictions of the afterlife and acts of filial piety. My study addresses both textual sources and ethnographic data, collected while conducting fieldwork during the summers of 2004 and 2005, to evaluate how these mythological theme parks culturally convey the past into the present.